Czech-Mexican trade cooperation with regard to cultural differences - Pokorná, Kristýna (2015)
The thesis deals with the Czech-Mexican trade cooperation with regard to cultural differences. The first chapter covers general characteristics of Mexico, desribes the political and legal environment, after that the infrastructure or telecommunications. The second chapter focuses on the economic characteristics of Mexico, provides analysis of basic indicators and sectors of Mexican economy. The third chapter describes trade betweeen the Czech Republic and Mexico, it also includes SWOT analysis of the Mexican market or data necessary for Czech exporters entry to Mexico. The fourth chapter outlines the differences between Czech and Mexican culture and the specifics of trade negotiations.